Effectiveness of Green Betel Leaf Powder (Piper betle L.) as a vegetable biopesticide against the Mortality of Rice Weevil (Sitophilus oryzae L.) - Febri Rizki Febri; Elimasni Elimasni; Erni Jumilawaty (Postgraduate, University of Mataram, 2024)
This study addresses the persistent challenge of rice storage and food security, focusing on the post-harvest management of stored grains, particularly in mitigating damage caused by the rice weevil (Sitophilus oryzae L.). The research explores the impact of varying concentrations (2-8 grams) of green betel leaf (Piper betle L.) powder extract on rice weevil mortality. Employing a Completely Randomized Design, the study reveals that the highest mortality (15.6%) is achieved with an 8-gram concentration of green betel leaf powder. Correlation analysis establishes a positive relationship between concentration and weevil mortality (r = 0.84), with a significant correlation (r = 0.77) between concentration and the time taken for weevil mortality. Calculated efficacy demonstrates that the 8 gram concentration achieves a 70% effectiveness, meeting success criteria. Consequently, green betel leaf powder emerges as a promising botanical insecticide against rice weevils, warranting further investigation for dosage optimization and concentration. Future research should prioritize environmental and human safety considerations in the development and application of botanical insecticides in agricultural pest management.